The Dynamics of Asymmetric Conflicts:: The Israeli-Palestinian Case - Gallo, Giorgio; Marzano, Arturo (Journal of Conflict Studies)

(untitled) (The University of New Brunswick, 2009)
ABSTRACT Asymmetry is considered one of the most relevant features in today’s conflicts. In this article we address one particular type of asymmetry — structural asymmetry. After introducing the main characteristics and different phases of these types of conflicts, i.e. conscientization, confrontation, negotiation, and sustainable peace, we address the specificity of the Israeli-Palestinian case presented here as a typical case of a structurally asymmetric conflict. The aim is to explain why, despite the many negotiation phases this conflict has been through, none has ever led to a sustainable peace. On the contrary, each negotiation has brought on yet another confrontation phase, in a never-ending series of loops. The strong imbalance between the two sides and the scarce reciprocal conflict awareness represent the two main reasons for explaining this pattern.